Multiple Primary Malignancies in Renal Transplant Recipients: a Single Centre Retrospective Cohort Study - Nikolina Basic-Jukic; Jason Kirincich; Bojan Jelakovic; Zeljko Kastelan (Karger Publishers, 2018)
Background/Aims: Renal transplant recipients are exposed to immunosuppressive treatment which may increase the risk for developing malignancies. Limited data exists concerning the occurrence of multiple primary malignancies (MPM) in renal transplant patients. Methods: All the patients who received a renal allograft at our institution from 1973 to 2017 were included in this investigation. Data from patients with more MPM were obtained from the charts and medical records. Malignancies were categorized as synchronous if the interval between occurrences was less than or equal to 6 months and metachronous if the interval was more than 6 months. Results: Out of the 1884 patients who received a renal allograft, 164 (8.7%) developed a malignant tumor. Twenty-two patients (13.4%; 6 females, 16 males) developed MPM, 7 synchronous (31.8%) and 15 metachronous types (68.2%). The most common initial primary tumors were skin cancers (8) and kidney cancers (3). Furthermore, skin cancers were the most common second primary malignancies (9). Log-rank analysis revealed significantly better survival in the synchronous group (113.3 months) than in the metachronous group (24.6 months) (p=0.04). Conclusion: MPM are more frequent in renal transplant recipients than in the general population. It is associated with a high mortality rate, especially in the metachronous group. An increased awareness and frequent screening tests are necessary when managing this condition.